Graft-versus-MDS effect after unrelated cord blood transplantation: a retrospective analysis of 752 patients registered at the Japanese Data Center for Hematopoietic Cell Transplantation - Ishiyama, Ken (Blood Cancer J, 2019)
Allogeneic hematopoietic stem cell transplantation is the sole curative therapy for myelodysplastic syndrome (MDS). However, there is concern regarding graft failure and relapse in patients who undergo cord blood transplantation (CBT). We conducted a retrospective study of the CBT outcomes in MDS patients using the Japanese Data Center for Hematopoietic Cell Transplantation database. Seven hundred fifty-two de novo MDS patients of ≥18 years of age (median, 58 years) undergoing their first CBT between 2001 and 2015 were examined. Two-thirds of the patients were male, and were RAEB. The cumulative incidences of neutrophil and platelet engraftment at day 100 were 77 and 59%, respectively. The 3-year overall survival (OS) was 41% and the median survival of the patients was 1.25 years. A multivariate analysis of pre-transplant variables showed that the age, gender, cytogenetic subgroups, number of RBC transfusions, HCT-CI and year of CBT significantly influenced the outcome. The cumulative incidence of acute graft-versus-host disease (aGVHD) and chronic GVHD (cGVHD) was 32 and 21%, respectively. A survival benefit was observed in patients who developed cGVHD, but not aGVHD. Our results suggest that CBT is an acceptable alternative graft and that a graft-versus-MDS effect can be expected, especially in patients who develop cGVHD.